2017
DOI: 10.24925/turjaf.v5i7.720-723.1092
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Some Drugs Used to Treat Honeybee (Apis mellifera L.) Diseases and Pests on Lifespan of Honeybees

Abstract: This study was conducted to determine the effects of Bayvarol®, Fumidil-B®, Neo-Terramycin® on adult honeybee lifespan. Total twenty honeybee colonies were used and randomly divided into four groups (each group consisted of five colonies). Experimental groups: Bayvarol ®, Fumidil-B® and Neo-Terramycin® were treated to first, second and third groups, respectively. No treatment was done to forth group taken as control group. A hundred one day old worker bees were taken from each group and marked with different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It has been shown that Fumagiline B induces alterations in the structural and metabolic proteins of the honeybee midgut at concentrations that do not suppress parasite multiplication [ 26 ]. It has also been shown to reduce honeybee lifespan [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Fumagiline B induces alterations in the structural and metabolic proteins of the honeybee midgut at concentrations that do not suppress parasite multiplication [ 26 ]. It has also been shown to reduce honeybee lifespan [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%